2016
DOI: 10.1371/journal.pone.0166120
|View full text |Cite
|
Sign up to set email alerts
|

Reference Genes for Addressing Gene Expression of Bladder Cancer Cell Models under Hypoxia: A Step Towards Transcriptomic Studies

Abstract: Highly aggressive, rapidly growing tumors contain significant areas of hypoxia or anoxia as a consequence of inadequate and/or irregular blood supply. During oxygen deprivation, tumor cells withstand a panoply of adaptive responses, including a shift towards anaerobic metabolism and the reprogramming of the transcriptome. One of the major mediators of the transcriptional hypoxic response is the hypoxia-inducible factor 1 (HIF-1), whose stabilization under hypoxia acts as an oncogenic stimulus contributing to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Rb1, a well-established suppressor of cell cycle entry, has been implicated in controlling terminal differentiation in many tissues, including the heart (38-40). Importantly, Rb1 is known to be regulated by hypoxia in cancer cells (44). Here we demonstrated that hypoxia modulates Rb1 activity, leading to chamber-specific induction of cell cycle genes in neonatal heart.…”
Section: Discussionmentioning
confidence: 59%
“…Rb1, a well-established suppressor of cell cycle entry, has been implicated in controlling terminal differentiation in many tissues, including the heart (38-40). Importantly, Rb1 is known to be regulated by hypoxia in cancer cells (44). Here we demonstrated that hypoxia modulates Rb1 activity, leading to chamber-specific induction of cell cycle genes in neonatal heart.…”
Section: Discussionmentioning
confidence: 59%
“…Because GAPDH has been reported to be induced by stress factors, such as oxidative and mechanical stress, 44 we validated the effect of oxidative stress, UV-B radiation, and mechanical stress on the expression of LOXL1-a and LOXL1 in hTCF and hTMC using HPRT as a stable reference gene. 45 The results were, however, not different from those using GAPDH as reference gene ( Supplementary Fig. S4).…”
Section: Nmd-coupled Alternative Splicing Is Modulated By External Stmentioning
confidence: 77%
“…33 34 In addition, studies are now also defining appropriate reference gene selection within tumour tissue and cancer cell lines. [35][36][37] Therefore, the aim of the present study was to define the impact of our FDG-MNPs in their non-magnetic stimulated state on tumour and non-tumour tissue in mice bearing MAC16 adenocarcinomas in a non-magnetic field environment. Here, we establish the expression profile of commonly used reference genes in a mouse adenocarcinoma model exposed to FDG-MNPs.…”
Section: Introductionmentioning
confidence: 99%